Determinants of the degradation of soil structure in vineyards with a view to conversion to organic farming. (22nd July 2013) - Polge de Combret ‐ Champart, L.; Guilpart, N.; Mérot, A.; Capillon, A.; Gary, C.
Abstract In perennial crops such as grapevine, there is a considerable risk of soil degradation caused by mechanization. Organic farming may increase traffic and result in more intensive soil structure degradation, especially on wet soil. Soil structure was observed in 69 soil profiles from 12 vineyards (Languedoc‐Roussillon, Bordeaux, Provence, Burgundy, Rhône Valley) to study the relationships between permanent soil characteristics (texture, stoniness, waterlogging), cultivation practices (technical operations, traffic, farm equipment) and soil structure. Compaction zones were identified in soil profiles viewed perpendicularly to the grapevine rows. The percentage of compacted area and a score for compaction intensity were assessed in the top 0.5 m of the soil profile in three soil compartments defined by the distance from the grapevine row: (1) 0 to 0.2 m (2) 0.2 m to 0.5 m and (3) 0.5 m to the middle of the inter‐row. Most soil profiles exhibited considerable compaction: 75% of the soil profiles were compacted in compartments 2 or 3. Intensity correlated with depth of compaction in compartment 2 – the deeper the compaction, the greater the compaction intensity. Four types of soil profiles could be identified, depending on the location of compacted zones and of their intensity of compaction. The factors that determined the types of soil profiles were as follows: soil vulnerability to compaction, use of moderating practices (practices that limit the risk of compaction) and traffic geometry. A statistical analysis resulted in a decision tree that provides a useful basis to choose cultivation practices that limit damage to or improve soil structure.